Legal Protection for Consumers Against the Purchase of Expired Products on the Market Based on Law No. 8 of 1999 Concerning Consumer Protection - Makmur Sigalingging; Sriono Sriono; Nimrot Siahaan (International Journal of Science and Environment (IJSE), 2025)
We often hear and see a series of cases related to the sale of Expired Products in the Market on television, almost all of which report on fraud committed by business actors in trade to deceive consumers as buyers of goods. This is not impossible to add to the series of similar cases, if the government does not take part in overcoming the circulation of expired products. The objectives of this study include: wanting to know how business actors are responsible for the circulation/sale of Expired Food and Beverage products and how to protect consumers against expired food and beverage products circulating in the market and consumed by consumers based on Law Number 8 of 1999 concerning Consumer Protection. The type of research used is normative research, while the approach uses a statutory approach. This study uses primary and secondary legal materials. Research Results and Discussion: First, the responsibility of business actors for dishonest trade towards consumers is through compensation with a refund of an amount of money according to the nominal traded, if the consumer has not yet consumed it, if they have consumed the consumer goods, and it has a bad effect on the consumer's health such as poisoning, or causes health problems, then the responsibility of the business actor will be greater, namely health recovery. according to Article 19 paragraph (2) of Law Number 8 of 1999. Second, Legal Protection for consumers has not been fully realized as stated in Law Number 8 of 1999 concerning consumer protection. This can be seen from the many business actors found in the market who are still distributing expired food and beverage products without supervision from the government and related agencies. The application of criminal penalties which is still not complete, of course, will not provide a deterrent effect for dishonest and fraudulent business actors.